Demand organization in public oral health services: analysis of a traditional model - Roncalli, Angelo Giuseppe; Moimaz, Suzely Adas Saliba; Gomes, Adrielle Mendes De Paula; Garbin, Cléa Adas Saliba; Saliba, Nemre Adas (Faculdade São Leopoldo Mandic, 2016)
ABSTRACTObjective: To discuss the municipal experience of the organization and the demand for dental services, based on the guidelines of the Unified Health System (UHS), which point to the structuring of an assistance model based on universality and integrality of care and equity in access to services.Methods: The research, realized in Araçatuba/SP, was based on documentary analysis and interviews with key-informants of the UHS dental service. The traditional court model has a care system for schoolchildren and a basic network with priority for pregnant women.Results: In total, the network has 59 dental surgeons, 31 oral health auxiliaries and 17 Oral Health Teams; however, the school attendance model persists, with 10 professionals attending public schools. Based on the discussions, it is concluded that there are no established criteria for the organization of demand.Conclusion: Most of the attendance occurs by free demand, and the reference and counter-referral system is incipient, damaging the service's resoluteness.

RESUMOObjetivo: Discutir a experiência municipal da organização a demanda de serviços odontológicos, com base nas diretrizes do Sistema Único de Saúde (SUS), as quais apontam para a estruturação de um modelo assistencial com base na universalidade e na integralidade da atenção e na equidade no acesso aos serviços.Métodos: A pesquisa, realizada em Araçatuba (SP), teve como base a análise documental e entrevistas com informantes-chave do serviço odontológico do SUS. O modelo de corte tradicional, conta com um sistema de assistência para escolares e uma rede básica com prioridade para gestantes.Resultados: No total, a rede conta com 59 cirurgiões-dentistas, 31 auxiliares em saúde bucal e 17 Equipes de Saúde Bucal, entretanto persiste o modelo de atendimento a escolar, com 10 profissionais atendendo em escolas públicas. A partir das discussões colocadas, conclui-se que, não há critérios estabelecidos para organização da demanda.Conclusão: A maioria dos atendimentos ocorre por livre demanda, e o sistema de referência e contra-referência é incipiente, prejudicando a resolutividade do serviço.
Organização da demanda em serviços públicos de saúde bucal: análise de um modelo tradicional
Keywords: Dental health services; Oral health; Public health; Unified Health System; Serviços de saúde bucal; Saúde pública; Saúde bucal; Sistema Único de Saúde